ORGANOLEPTIK WAFER DENGAN BERBAGAI KOMPOSISI LIMBAH PERTANIAN DI DESA BANDAR BARU KECAMATAN SUKAU KABUPATEN LAMPUNG BARAT - Tias Pratama; Farida Fathul; Muhtarudin . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The purpose of this study was to determine texture, color, aroma, and palatability wafers with various agricultural waste compotition. The experimental design used in this research is completely randomized design (CRD) with three treatments and four replications. Wafer agricultural waste consists of three treatments and four replications, namely A: sweet potato 8% + potato 3% + cauliflower leaf chicory 5% + china cabbage 10%+ carrots 50% +labusiam 5% + tomato 15.99% + molasses 3 % + salt 0.01%; B: sweet potato 15% + potato 5% + leaf cauliflower chicory 10% + China cabbage 15% + carrot 40% + labusiam 6% + tomato 5.99% + molasses 3% + salt 0.01%; C: sweet potato 20% + potato 7% + cauliflower leaf chicory 15% + China cabbage 20% + carrot 23% +labusiam 8% + tomato 3.99% + molasses 3% + salt 0.01%. The results of this study indicate that the wafer with a variety of agricultural waste composition was highly significant (P <0.01) on the color and texture of the resulting wafer, wafer agricultural waste significant (P <0.05) on the scent wafers produced. Best palatability generated on wafer composition C.